Molecular mechanisms underlying the potential antiobesity-related diseases effect of cocoa polyphenols - Ali, Faisal; Ismail, Amin; Kersten, Sander (Wiley-VCH Verlag, 2014)
Obesity and related metabolic diseases (e.g., type 2 diabetes, cardiovascular diseases, and hypertension) are the most prevailing nutrition-related issues in the world. An emerging feature of obesity is their relationship with chronic inflammation that begins in white adipose tissue and eventually becomes systemic. One potential dietary strategy to reduce glucose intolerance and inflammation is consumption of polyphenol-rich cocoa-like cocoa or their by-products. In vitro as well as in vivo data indicate that cocoa polyphenols (CPs) may exhibit antioxidant and anti-inflammatory properties. Polyphenols commonly found in cocoa have been reported to regulate lipid metabolism via inducing metabolic gene expression or activating transcription factors that regulate the expression of numerous genes, many of which play an important role in energy metabolism. Currently, several molecular targets (e.g., nuclear factor Kappa B, activated protein-1, peroxisome proliferator-activated receptors, liver X receptors, and adiponectin gene) have been identified, which may explain potential beneficial obesity-associated diseases effects of CPs. Further studies have been performed regarding the protective effects of CPs against metabolic diseases by suppressing transcription factors that antagonize lipid accumulation. Thus, polyphenols-rich cocoa products may diminish obesity-mediated metabolic diseases by multiple mechanisms, thereby attenuating chronic inflammation.